РSYCHOLOGICAL ASРECTS OF THE РROBLEM OF ARTIFICIAL INTELLIGENCE - Zuhra Mo‘minxo‘jayeva (Journals Park Publishing, 2025)
In this article, the emergence and historical development of the artificial intelligence problem, as well as current trends in engineering psychology, ergonomics, and general psychology, are briefly analyzed. The discussion highlights the necessity of considering the interaction between humans and the regulated evolutionary environment in the creation of artificial intelligence systems and technologies that have emerged within the technogenic environment of human civilization. Within the frameworks of postclassical psychology and the philosophy of complex self-organizing systems, the article explores promising research directions and challenges related to the use of conceptual apparatus in these fields.
Keywords: Intellect, artificial intelligence, postclassical psychology, self-organization.